2019
DOI: 10.1016/j.jpha.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic evaluation, molecular docking and in vitro biological evaluation of 1, 3, 4-oxadiazole derivatives as potent antioxidants and STAT3 inhibitors

Abstract: 1, 3, 4-Oxadiazole derivatives (4a–5f) were previously synthesized to investigate their anticancer properties. However, studies relating to their antioxidant potential and signal transducer and activator of transcription (STAT) inhibition have not been performed. We investigated previously synthesized 1, 3, 4-oxadiazole derivatives ( 4a–5f) for various radical scavenging properties using several in vitro antioxidant assays and also for direct inhibition of STAT3 th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…The predictive studies using the PASS application indicated the inhibition of the STAT3 transcription factor as the most probable anticancer mechanism. Recent evidence shows that the 1,3,4-oxadiazole scaffold is frequently used in the structure of STAT3 inhibitors active against various cancer cells [ 39 , 40 , 41 ]. STAT3 is closely related to the occurrence of cancers and is an attractive therapeutic target for oncology and drug development.…”
Section: Discussionmentioning
confidence: 99%
“…The predictive studies using the PASS application indicated the inhibition of the STAT3 transcription factor as the most probable anticancer mechanism. Recent evidence shows that the 1,3,4-oxadiazole scaffold is frequently used in the structure of STAT3 inhibitors active against various cancer cells [ 39 , 40 , 41 ]. STAT3 is closely related to the occurrence of cancers and is an attractive therapeutic target for oncology and drug development.…”
Section: Discussionmentioning
confidence: 99%
“…Fathi and coworkers reported the anticancer and STAT3-inhibitory activity of oxadiazole conjugated chalcones [ 48 ]. Khanam and team identified a 1,3,4-oxadiazole derivative that directly interacts with the SH2 domain of STAT3 in docking analysis and direct binding studies [ 49 ]. Collectively, these studies proposed that the conjugation of 1,3,4-oxadiazole moiety with other heterocycle yield new structures with STAT3 inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the authors further expanded the therapeutic efficacy of ODZ10117 in glioblastoma by targeting STAT3 . Similarly, Khanam et al identified a 1,3,4-oxadiazole derivative 87 as a STAT3 inhibitor by screening their previously synthesized compounds . AlphaScree-based assays revealed 87 strongly interacted with the SH2 domain and exhibited significant activity against STAT3 (74.12% of inhibition at 60 μg/mL concentration).…”
Section: Recent Development Of Stat3 Inhibitorsmentioning
confidence: 99%
“…As shown above, the oxadiazole ring in STX-0119 emerged as a key molecular feature for STAT3 inhibition. , Using structure-based computational database screening coupled to cell-based high-throughput screening, Kim et al also discovered oxadiazole-based ODZ10117 ( 86 , Figure ) as a specific STAT3 inhibitor . In comparison with the known STAT3 inhibitors S3I-201, STA-21, and nifuroxazide, ODZ10117 has a greater inhibition on STAT3 activation via directly blocking the SH2 domain of STAT3 and thereafter suppressing its homodimerization and transcriptional activity, which mediated its diverse anticancer effects against breast cancer cells including apoptosis induction as well as reduction of migration and invasion.…”
Section: Recent Development Of Stat3 Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation